The gospel according to Sayyid Ahmad Khan (1817-1898) : an annotated translation of Tabyīn al-kalām (part 3) - Troll, Christian W., 1937- (The History of Christian-Muslim Relations, 2020)
"The Gospel According to Sayyid Ahmad Khan (1817-1898) offers an annotated translation of Tabyīn al-kalām (Part 3), a commentary on the Gospel of St. Matthew (Chapters 1-5) by one of South Asia's most innovative public thinkers. Broadly known for his modernist interpretation of Islam, Sayyid Ahmad Khan (1817-1898) appears here as a contemplative mystic who is determined to show the interrelated nature of the Bible and Qur'ān, and the affinity of Christian and Muslim scriptural exegesis. Uncommon in the history of Christian-Muslim relations, Sayyid Ahmad Khan presents what can only be described as a serious reading of the Gospel. The work includes an extensive introduction to the early Church in general, and the development of the Trinitarian doctrine in particular. Never before presented in English, the text sheds important new light upon the spiritual and intellectual journey of this leading modern interpreter".